Application of smart nano-WBM material for filtrate loss recovery in wellbores with tight spots problem: an empirical study - Zamani, A. (Springer Verlag, 2018)
There is no deep understanding of the application of nanoparticles in water-based muds (WBM). Therefore, such study that helps to enhance the knowledge in the field of well stability using modern methods in an unforgiving industry is very much needed. The nanoparticles accumulate on the wellbore wall and due to their very small sizes, they seal the pores in the mud cake, which plasters the wellbore. This paper focuses on empirical aspects of using nano-bentonite for filter loss control. The current work was applied on a nano-drilling fluid to improve filtration characteristics of drilling fluid in the wellbore. Therefore, nano-bentonite WBM (size between 90 and 100 nm) was introduced as the smart drilling fluid with abilities to overcome the tight spot problem in wellbores, which has been investigated in the paper. Three different drilling fluids were prepared using nano-bentonite clay with the main focus of enhancing those rheological features of the fluid expected to improve the mud characteristics, especially the plastering properties. Low pressure low temperature (LPLT) filter press test has been utilized to calculate the filter loss volume and the viscosity, yield point and gel strength of the understudy samples and the results have been compared. It was found that the filtration loss during the LPLT test was reduced by an overall average of 34 for all of the three samples, resulting in better filtration characteristics. Â© 2018 The Author(s)